Three essays on Indonesia's economic development - Nugroho, Wisnu Setiadi, author; Pena, Anita A., advisor; Barbier, Edward B., committee member; Mushinski, David, committee member; Kroll, Stephan, committee member (Colorado State University. Libraries, 2022)
To view the abstract, please see the full text of the document.
Keywords: Indonesia; poverty trap; universal health care; microdata surveys; gendered education spending; Timor-Leste